How software development competences change in global settings—an explorative study. Issue 1 (30th December 2014) - Holtkamp, Philipp; Lau, Ivan; Pawlowski, Jan Martin
Abstract Global software development (GSD) holds various challenges and problems for team members. When confronted with a contextual change in their working environment, individuals have to adapt to the new situation. This includes the adaptation of working styles, behaviors, and methods. Additionally, new challenges, especially those based on the virtual work and cultural background of team members, have to be addressed. By conducting explorative expert interviews, we identified challenges and potential solutions for individuals when encountering contextual change with a focus on competences. We identified that the lack of competences was seen as a major influence factor for a variety of common challenges to GSD. The identification of underlying factors of challenges could allow for focused development of interventions to overcome these challenges. Furthermore, we identified factors influencing the adaptation of competences to the given context and provided insight into the process of competences adaptation. This is the basis for the future development of a set of internationalized GSD competences. Copyright © 2014 John Wiley & Sons, Ltd.